2019
DOI: 10.1111/ijpo.12518
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with depression and anxiety symptoms among children seeking treatment for obesity: A social‐ecological approach

Abstract: Summary Background Children with overweight/obesity are more likely to exhibit symptoms of depression and anxiety than are their peers without overweight/obesity; however, the rates and correlates of depression and anxiety symptoms among children seeking obesity treatment remain unclear. Objectives Examine the prevalence and associated factors of depression and anxiety symptoms among treatment‐seeking children with overweight/obesity. Methods Children 7 to 11 years old (N = 241) and their parents completed ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 45 publications
(107 reference statements)
1
11
0
1
Order By: Relevance
“…Community norms for youth ages 12–14 are available (Carter, Stewart, & Fairburn, 2001), but psychometric properties of the EDE‐A have not been examined. In contrast, the YEDE‐Q has been used primarily in overweight populations (Balantekin et al, 2017; Eichen et al, 2019; Kass et al, 2017; Sheinbein et al, 2019; Skjåkødegård et al, 2016). Only one study of eating disorders was identified that used the YEDE‐Q, which demonstrated some evidence of convergent validity in adolescent inpatients with AN (Noetel et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Community norms for youth ages 12–14 are available (Carter, Stewart, & Fairburn, 2001), but psychometric properties of the EDE‐A have not been examined. In contrast, the YEDE‐Q has been used primarily in overweight populations (Balantekin et al, 2017; Eichen et al, 2019; Kass et al, 2017; Sheinbein et al, 2019; Skjåkødegård et al, 2016). Only one study of eating disorders was identified that used the YEDE‐Q, which demonstrated some evidence of convergent validity in adolescent inpatients with AN (Noetel et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In reaction to anxiety, emotional eating acts as a biological response that provides temporary feelings of gratification/satisfaction [57]. The intervention approach for children with anxiety symptoms and emotional eating should be adapted to address the negative emotions underlying eating behaviors as well as teaching healthy coping strategies for these emotions [58]. Parents and their own perception of the child's dietary habits is one of the most important factors for the dietary habits of children [59].…”
Section: Subjective Perception Of Eating Habits Dimensionmentioning
confidence: 99%
“…Body mass index (BMI) is the weight‐to‐height ratio, where an increased BMI, specific to growth standards of a population, is indicative of overweight and obesity in the population (WHO, 2018). Being obese or overweight among youth are associated with a plethora of adverse physical, psychosocial, and psychological consequences (Li et al, 2020; Sheinbein et al, 2019), one of them being increased risk of being bullied (Van Geel et al, 2014; Waasdorp et al, 2018). However, these results were mostly based on cross‐sectional designs that do not allow for analysis of directionality of relations, and the few longitudinal studies that have examined the direction of links have reported inconsistent results (Adams & Bukowski, 2008; Baldwin et al, 2016; Lee et al, 2018; Lumeng et al, 2010).…”
Section: Introductionmentioning
confidence: 99%